Pembentukan Kelas Ibu Remaja di Kelurahan Sungai Putri Kota Jambi - Ratu Kusuma; Armina Armina; Hesty Hesty; Fitri Dyna; Afrida Sriyani Harahap; Dini Maulinda; Siska Rahmadiya; Desti Puswati; Yureya Nita; Veny Dayu Putri; Sri Yanti (Jurnal Abdimas Kesehatan (JAK), 2026)
Putri Ayu Public Health Center is one of the 20 health centers in Jambi City that has a significantly high number of adolescent pregnancy cases. Over the last five years (2020-2024), there were 164 cases of adolescent pregnancy. Specifically, there were 33 cases in 2020, 33 in 2021, 35 in 2022, 31 in 2023, and 32 in 2024. Among these cases, eight pregnancies involved adolescents aged 14-15 years. Therefore, a team of lecturers and students from Baiturrahim University felt the need to conduct a community service activity in the form of establishing an Adolescent Mother Class in Sungai Putri Sub-district, Jambi City, through a mini-workshop. The community service activity ran from September 2024 to February 2025. The mini-workshop and the establishment of the Adolescent Mother Class were held on Saturday, February 8, 2025, at the "Putri Kencana" KB Village Secretariat Post, RT 16, Sungai Putri Sub-district, Jambi City. The goal was to increase knowledge and change attitudes regarding adolescent pregnancy and its various issues, the importance of forming the class, and the eventual establishment of an Adolescent Mother Class, even a simple one. The mini-workshop was attended by 7 out of the 11 targeted adolescent mothers and was conducted for one day (3-4 hours). The materials were delivered through lectures, discussions, Q&A sessions, and experience sharing, using PowerPoint presentations displayed via a projector. A pre-test and post-test were administered before and after the mini-workshop. Following the activity, the average knowledge score increased by 1.6 points, and the attitude score increased by 5.0 points. It is concluded that the formation of the Adolescent Mother Class is highly crucial in changing the behavior (knowledge, attitude, and action) of these young mothers